Peran BMT Mandiri Artha Syariah Dalam Pemberdayaan UMKM Di Kabupaten Bojonegoro Pada Masa Pandemi Covid-19 - Bistiana, Mila; Indrarini, Rachma (Universitas Negeri Surabaya, 2021)
With the decline in the economy during the Covid-19 pandemic, MSME faces some difficulties in their businesses. This study aims to determine the role of BMT Mandiri Artha Syariah in empowering MSME both before and during the Covid-19 pandemic. To get research results that can interpret the role of BMT in empowering MSME, researchers used a descriptive qualitative approach. BMT Mandiri Artha Syariah Bojonegoro is the object in this research . Sources of data in this study are primary and secondary data. Primary data is data obtained by researchers directly from informants. And secondary data is data obtained by researchers indirectly from books and journals that support research. The data validity technique used in this study was the source triangulation technique and the technique triangulation. The data analysis technique uses the Analysis Interactive model from Miles and Huberman consisting of data collection, data reduction, data presentation, and conclusion making. The result shows that MSMEs funding program in BMT Artha is already run well, but there are some services need to be noticed. Before the Covid-19 outbreak, funding program was running well. But in this pandemic, a lot of MSMEs experience default that BMT Artha provide leeway in payment times and become selective in providing the funding program.